Non-equilibrium dynamics of tunnel-coupled superfluids : relaxation to a phase-locked equilibrium state in a one-dimensional Bosonic Josephson Junction /: relaxation to a phase-locked equilibrium state in a one-dimensional Bosonic Josephson Junction. ([2020]) - Pigneur, Marine
No abstract available